A Comparative Study of Sentence Building in Writing Ability Among Students in Indonesia - Sari Famularsih; Muhammad Irfan Helmy (State Institute for Islamic Studies IAIN of Metro, 2020)
This research focuses on a comparative study of sentence building between the better students (more knowledgeable) and the novice students (less knowledgeable) in writing 1 class. It belongs to qualitative research involving two respondents of the better and the novice students. Three questions emerge in this research related to the dominant sentence types between the better and the novice students, the challenges and strategies in writing. Those questions are (1) What types of sentences dominate the building of the sentence of novice and better students? (2) What are the challenges in writing between novice and better students?, and (3) What are the students’ strategies in writing?. In order to answer those three research questions, I run two methods of data collection. The first one is email observation, which tries to find an answer to the dominant sentence types of the better and the novice students. The second method is a face-to-face interview to get more in-depth insight and understanding of the challenges and strategies in writing. As a result, the better student surprisingly dominates her paragraph writing assignments with complex sentences that show her advanced writing skills as the effect of her writing practice. Meanwhile, the novice one mostly occupies simple sentences to avoid errors because she has an inadequate practice that exposes her fear. In terms of challenges, this study finds five items, including the complex process of writing, anxiety, and panic, time constraints, grammar, and vocabulary. In the case of writing strategies, the finding reveals four items, such as short writing, frequent writing, dictionary usage, and reading practice.